Chemotherapeutic alteration of VEGF-/PDGF- and PDGF-Rα/β expression by imatinib in HPV-transformed squamous cell carcinoma compared to HPV-negative HNSCC in vitro - Schultz, Johannes D.; Kölbel, Kathrin Anna; Erben, Philipp; Hofheinz, Ralf-Dieter; Lammert, Anne; Thorn, Carsten Volker; Sommer, Ulrich; Hörmann, Karl; Sauter, Alexander (Oncology reports, 2011)
Head and neck squamous cell carcinoma (HNSCC) is an aggressive epithelial malignancy known to be the most common neoplasm appearing in the upper aerodigestive tract. The poor five-year survival rate has remained unchanged in the last decades despite the emergence of improved techniques in surgery, radiation and chemotherapy. In the last 20 years awareness of a subset of squamous cell carcinomas induced by oncogenic forms of the human papilloma virus (HPV) (high-risk types 16 and 18) has increased. The incidence of HPV-associated oropharyngeal cancer is rising, indicating the increased importance of the viral etiology. Cell proliferation, migration, induction of tumor vascularization and carcinogenesis, as well as invasion facilitation is regulated by a variety of angiogenic peptides like PDGF, PDGF-R and VEGF. They might be an encouraging target for biological anticancer therapy by inhibiting disrupted cellular signaling pathways. Imatinib has been shown to target specific tyrosine kinases, inhibiting proliferation in various cancer entities. The purpose of this study was to evaluate the expression pattern of angiogenic factors (VEGF, PDGF and PDGF-R) in HPV-positive (p16-CERV196 SCC) and (-negative squamous cell carcinoma (HNSCC). The study also evaluated the vulnerability of anti-angiogenesis therapy depending on the HPV status as potential treatment modality compared to established platinum-based chemotherapeutic drugs. The different squamous tumor cell lines were incubated with increasing concentrations of carboplatin (3 and 7.5 µmol) and imatinib (18 and 30 µmol). ELISA immunohistochemical methods were carried out after 48, 72, 120, 192 and 240 h. We demonstrated a significant reduction of VEGF and PDGF-Rα/β expression patterns after incubation of imatinib in ELISA and immunohistochemical methods, irrespective of the HPV status of the tumor cells, whereas the application of carboplatin had no impact on the expression of angiogenic peptides. Viral oncogen-transformed squamous cell carcinoma (CERV196) cells were characterized by a reduced susceptibility for an imatinib-altered VEGF expression. Further studies are planned to investigate this observance in HPV-positive HNSCC in vitro. The implementation of a selective molecular anti-angiogenic therapy in established chemotherapeutic regimens may enhance the efficacy of platinum-based chemotherapy without an increased toxicity profile and could thus improve the clinical outcome in HNSCC, irrespective of the HPV status.